Efficacy of omalizumab treatment for patients with chronic idiopathic urticaria (CIU)/chronic spontaneous urticaria (CSU) in Taiwan - Che-Wen Yang; Yung-Tsu Cho; Chia-Yu Chu (Wolters Kluwer Medknow Publications, 2017)
Background/Objectives: Accumulating evidence has shown that omalizumab is an effective and safe treatment for chronic spontaneous urticaria (CSU), but there is little information regarding the use of omalizumab to treat CSU in Taiwan. Reports on clinical experiences with using omalizumab for CSU for more than 6 months are also lacking. Methods: A retrospective review of medical records of consecutive CSU patients receiving omalizumab treatment in the Urticaria Special Clinic of one tertiary referral center in Taiwan was conducted. We analyzed clinical features of the patients, treatment efficacy and safety, and also long-term outcomes after omalizumab treatment. An Urticaria Activity Score over 7 days (UAS7) was recorded at each visit. Results: A total of 17 CSU patients were identified (11 females and 6 males, age range: 21-83 years) with a baseline mean UAS7 of 29.8 ± 8.9 despite antihistamine treatment. All patients were treated with at least 3 doses of monthly subcutaneous injections of omalizumab. Fifteen patients achieved a UAS7 of 6 or less after 3 doses of monthly omalizumab injections. Seven of those 15 patients received an additional 1 to 3 doses and all ended up with a UAS7 of less than 2 at the 24-week follow-up. A sustained response to maintenance treatment after 24 weeks was observed in 5 patients with individual tailoring of treatment duration and dosing interval. Conclusion: Omalizumab is an effective and safe treatment for antihistamine refractory CSU. Maintenance therapy with individual tailoring of the treatment duration and interval is possible.